Modified Model Predictive Control of a Bidirectional AC-DC Converter Based on Lyapunov Function for Energy Storage Systems - Parvez Akter M.; Mekhilef S.; Mei Lin Tan N.; Akagi H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Delay control systems; Electric energy storage; Energy storage; Lyapunov functions; Lyapunov methods; Model predictive control; Power converters; Renewable energy resources; System stability; Time delay; Ac-dc power conversion; Conventional modeling; Direct Lyapunov methods; Energy storage systems; Modified model; Renewable energy source; Stability analysis; Three-phase ac voltage; Rectifying circuits